Analisis Data ADS-B untuk Menentukan Probability of Target Report pada Sistem A-SMGCS - I Made Astawa; I Putu Ananta Yogiswara; Tahar Agastani; Afrias Sarotama (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2019)
A-SMGCS is an airport system that is used to improve the efficiency of using runways, apron and taxiways by maximizing runway capacities in all situations and weather while maintaining the required level of security. One of the parameters that becomes a requirement in the A-SMGCS system is the Probabillity of Target Report (PTR) whose value must be greater or equal to 95% in the area maneuver with update rate of the data one second [1]. Automatic Dependent SurveillanceBroadcast (ADS-B) is one of the cooperative sensors in the A-SMGCS system. The ADS-B sensor is a receiver that is used to capture ADS-B data from aircraft or vehicles equipped with ADS-B transmitters. The amount of ADSB data received by the ADS-B receiver and is needed for the A-SMGCS system is one of the factors that determine the Probability of Target Report (PTR). This paper will test three ADS-B receivers which will be selected for use as a cooperative sensor in the next A-SMGCS development. From the results of analysis and retrieval of data obtained by Radarcape ADS-B receiver more suitable for the development of the A-SMGCS system.